Penerapan Model Think Talk Write Berbasis Multimedia Terhadap Kemampuan Pemahaman Konsep Dan Komunikasi Matematis - Alfania, Alfania (Pendidikan Matematika Universitas PGRI Yogyakarta, 2019)
AbstractTTW learning model assisted multimedia was applied to help students in developing their conceptual understanding and mathematical communication skills. This research was conducted to determine whether there was difference of effect between the application of TTW model assisted multimedia and peer tutoring model on the two mathematical skills. This research was a quantitative research with nonequivalent posttest-only control group design. The research population were the students of XI MIA at MAN 1 Pekalongan 2018/2019. The research sample was obtained by cluster sampling technique. The method used in collecting the data was a test. The data were analyzed by using the multivariate and univariate average difference test. The research results showed that (1) based on multivariate analysis, students’ conceptual understanding and mathematical communication skills that was taught by using TTW model assisted multimedia was different with students who were taught by using peer tutoring model; (2) based on univariate analysis, students’ conceptual understanding skills that was taught by using TTW model assisted multimedia was different with students who were taught by using peer tutoring model, and students’ mathematical communication skills that was taught by using TTW model assisted multimedia was different with students who were taught by using peer tutoring model. Keywords: TTW, Multimedia, Conceptual Understanding, Mathematical Communication